2016
DOI: 10.1016/j.canlet.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics: A systems biology approach to understanding genetic risk factors for radiotherapy toxicity?

Abstract: Adverse reactions in normal tissue after radiotherapy (RT) limit the dose that can be given to tumour cells. Since 80% of individual variation in clinical response is estimated to be caused by patient-related factors, identifying these factors might allow prediction of patients with increased risk of developing severe reactions. While inactivation of cell renewal is considered a major cause of toxicity in early-reacting normal tissues, complex interactions involving multiple cell types, cytokines, and hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 217 publications
(224 reference statements)
1
61
0
1
Order By: Relevance
“…Thus, ATM plays a crucial role in the biological response to ionizing radiation and influences the fate of the cell following irradiation [16]. Acute radiation toxicity typically takes place in skin or mucosal membranes and its pathogenesis is assumed to involve depletion of rapidly dividing cells in the basal layer [12]. In our meta-analysis, the rs1801516 SNP had a stronger impact on acute than late toxicity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, ATM plays a crucial role in the biological response to ionizing radiation and influences the fate of the cell following irradiation [16]. Acute radiation toxicity typically takes place in skin or mucosal membranes and its pathogenesis is assumed to involve depletion of rapidly dividing cells in the basal layer [12]. In our meta-analysis, the rs1801516 SNP had a stronger impact on acute than late toxicity.…”
Section: Discussionmentioning
confidence: 85%
“…The vast majority of these studies has been underpowered to detect the small effect sizes usually found for SNPs [10]. Even though numerous significant associations were reported [1012], only very few of these have been independently confirmed [13,14]. The gene product of ATM plays a crucial role in biological response to ionizing radiation.…”
mentioning
confidence: 99%
“…Genetic variations influence sensitivity to genotoxic stress, the detrimental effects of radiation treatment, and the prognosis of radiation therapy [83][84][85][86][87][88][89][90][91][92]. We hypothesized that Drosophila with naturally occurring genetic variations might reveal novel pathways that enhance stem cell proliferative repair and reduce radiation-induced intestinal permeability.…”
Section: Fly Gwas (Genome-wide Association Study) For Radiation-inducmentioning
confidence: 99%
“…Furthermore, several potential biomarkers such as pulmonary function, dose–volume histogram, end/pre-RT plasma levels of TGF-β1, IL1α, and IL6 have been described that may be suited to predict a higher risk for radiation-induced lung toxicity (226, 227). A promising novel approach to predict and understand genetic risk factors for radiation-induced toxicity may be the use of radiogenomics (228). …”
Section: Therapeutic Approaches For Radiation-induced Pneumopathymentioning
confidence: 99%